Report of a Novel Mutation in MLH1 Gene in a Hispanic Family from Puerto Rico Fulfilling Classic Amsterdam Criteria for Lynch Syndrome - Juan M. Marqués-Lespier; Yaritza Diaz-Algorri; Maria Gonzalez-Pons; Marcia Cruz-Correa (Gastroenterology Research and Practice)
In Puerto Rico, colorectal cancer (CRC) represents the second leading cause of cancer in men and women. Familial CRC accounts for 10–15% of the total CRC cases, while Lynch syndrome accounts for approximately 2–4% of cases. Limited information is available about the prevalence, clinical manifestations, and genetic mutations of hereditary CRC in US Hispanic individuals. In this paper we report a novel mutation in the hMLH1 gene in a Puerto Rican Hispanic family with Lynch syndrome recruited through the Puerto Rico Familial Colorectal Cancer Registry (PURIFICAR). Our proband was identified by applying Amsterdam and Bethesda criteria for Lynch syndrome, analysis of protein expression by immunohistochemistry, and genetic sequencing of the mismatch repair genes. A novel mutation at c.2044_2045 in hMLH1 consisting of the deletion of two consecutive nucleotides (AT) at exon 18 was identified. This deletion causes a frameshift in the protein coding sequence at p.682 resulting in premature termination and a truncated MLH1 protein. To our knowledge, this mutation has not been previously reported in the literature. The detection of this novel mutation in MLH1 further emphasizes the need for genetic testing in at-risk patients for hereditary CRC from various ethnic and racial backgrounds.